Extraction of Natural Gum from Cold-Pressed Chia Seed, Flaxseed, and Rocket Seed Oil By-Product and Application in Low Fat Vegan Mayonnaise - Hijazi, Taha; Karasu, Salih; Tekin-Cakmak, Zeynep Hazal; Bozkurt, Fatih (MDPI, 2022)
This study involves the modeling of rheological behavior of the gum solution obtained from cold-pressed chia seed (CSG), flaxseed (FSG), and rocket seed (RSG) oil by-products and the application of these gums in a low-fat vegan mayonnaise formulation as fat replacers and emulsifier. CSG, FSG, and RSG solutions showed shear-thinning flow behavior at all concentrations. The K values ranged between 0.209 and 49.028 Pa center dot s(n) for CSG, FSG, and RSG solutions and significantly increased with increased gum concentration. The percentage recovery for the G ' was significantly affected by gum type and concentrations. CSG, FSG, and RSG showed a solid-like structure, and the storage modulus (G ') was higher than the loss modulus (G '') in all frequency ranges. The rheological characterization indicated that CSG, FSG, and RSG could be evaluated as thickeners and gelling agents in the food industry. In addition, the rheological properties, zeta potential, and particle size and oxidative stability (at 90 degrees C) of low-fat vegan mayonnaise samples prepared with CSG, FSG, and RSG were compared to samples prepared with guar gum (GG), Arabic gum (AG), and xanthan gum (XG). As a result, CSG, FSG, and RSG could be utilized for low-fat vegan mayonnaise as fat and egg replacers, stabilizers, and oxidative agents. The results of this study indicated that this study could offer a new perspective in adding value to flaxseed, chia seed, and rocket seed cold-press oil by-product.
Keywords: cold-pressed oil by-product; gum; thixotropic behavior; low-fat vegan mayonnaise; thickeners; gelling agents; SHEAR-FLOW PROPERTIES; RHEOLOGICAL PROPERTIES; PHYSICOCHEMICAL PROPERTIES; STRUCTURAL-CHARACTERIZATION; OXIDATIVE STABILITY; GUAR GUM; BEHAVIOR; POLYSACCHARIDE; STEADY; TEMPERATURE; Food Science & Technology